2003
DOI: 10.1103/physrevd.67.083513
|View full text |Cite
|
Sign up to set email alerts
|

Interacting quintessence solution to the coincidence problem

Abstract: We show that a suitable interaction between a scalar field and a matter fluid in a spatially homogeneous and isotropic spacetime can drive the transition from a matter dominated era to an accelerated expansion phase and simultaneously solve the coincidence problem of our present Universe. For this purpose we study the evolution of the energy density ratio of these two components.We demonstrate that a stationary attractor solution is compatible with an accelerated expansion of the Universe. We extend this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
512
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 508 publications
(526 citation statements)
references
References 63 publications
(58 reference statements)
13
512
1
Order By: Relevance
“…Similar to natural inflation [107], it has been proposed that the flatness of the quintessnce potential could be protected by the field being a pseudo-Nambu-Goldstone boson [108,109]. Additionally, it has been proposed that dark energy and inflation can both be driven by the same field [110][111][112][113][114][115][116][117][118] Quintessence models have a rich phenomenology; one of the more interesting phenomena is that-by suitably choosing the potential-the energy density in the quintessence field can be made to "track" the energy density in radiation/matter at early times and then grow to dominate the energy budget at late times [119][120][121][122][123][124][125][126]. The canonical example of a potential that produces this behavior is the Ratra-Peebles potential [67] V (φ) = M 4+n φ n , (2.4) where n > 0 is a constant.…”
Section: (23)mentioning
confidence: 99%
“…Similar to natural inflation [107], it has been proposed that the flatness of the quintessnce potential could be protected by the field being a pseudo-Nambu-Goldstone boson [108,109]. Additionally, it has been proposed that dark energy and inflation can both be driven by the same field [110][111][112][113][114][115][116][117][118] Quintessence models have a rich phenomenology; one of the more interesting phenomena is that-by suitably choosing the potential-the energy density in the quintessence field can be made to "track" the energy density in radiation/matter at early times and then grow to dominate the energy budget at late times [119][120][121][122][123][124][125][126]. The canonical example of a potential that produces this behavior is the Ratra-Peebles potential [67] V (φ) = M 4+n φ n , (2.4) where n > 0 is a constant.…”
Section: (23)mentioning
confidence: 99%
“…Recently, it has been shown that the ω > −1 to ω < −1 transition always occurs in the quintom models with slowly-varying potentials [9]. Also if one considers one scalar field, but with suitable interaction with background dark matter, again this transition can be occurred [10].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, Eq. (2.16) can be obtained by combining the time derivative of (2.10) with (2.13) yieldinġ 19) withR ≡ σ ij R ij and analogouslyπ = σ ij π ij . Terms in expressions (2.16) and (2.19) can be matched using Codazzi-Gauss equations.…”
Section: Local Propagation and Constraint Equationsmentioning
confidence: 99%
“…There are strong theoretical arguments to take into account scalar-tensor theories, including the fact that scalar partners of the graviton naturally arise in most attempts to quantise or unify gravity with other interactions and that the coupling between the scalar field and the matter density could provide a mechanism to alleviate the coincidence problem [19]. Scalar-tensor theories are usually formulated in two different frames: the Jordan Frame (JF) and the Einstein Frame (EF).…”
Section: Introductionmentioning
confidence: 99%